Atypical Interaction: Conversation Analysis and Communicative Impairments. Issue 3 (3rd July 2019) - Wilkinson, Ray
ABSTRACT: In this article I review conversation analytic work on "atypical interaction"—social interactions where a participant has a communicative impairment. Drawing together some of the main themes and findings in the field, I highlight three forms of atypicality in these interactions, with each linked to more than one type of communicative impairment: (a) atypical forms of delay in TCU progressivity; (b) atypical problems of understandability, intelligibility, and hearing; and (c) atypical actions. I also discuss forms of atypicality that appear to arise from one or more participants adapting their talk or conduct to deal with the impact of the impairment within interaction. The article concludes with some considerations of directions that future work in this field might take. Data are in British and Australian English.